Service brand equity and employee brand commitment - Narumon Kimpakorn (2018)
Purpose: The aims of this article are to measure the brand equity of service firms (luxury hotels) using a customer perspective, to identify factors that predict customers' brands relationships and to explore the links between service brand equity and employee brand commitment Design/methodology/approach: Two surveys were conducted to achieve the research objectives. The first survey objective was to measure brand equity using a sample of 250 international customers of five-star hotels in Bangkok. The second survey objective was to collect information regarding employee brand commitment in each selected hotel using a sample of 250 employees. Findings: Results show that hotels belonging to the same category have different brand equity and that brand differentiation and brand trust are the variables that have the major influence on customer brand relationships. Perceived service quality and associations related to hotel core services are not related to brand relationships. High hotel brands equity have a stronger level of employee brand commitment that low hotel brands equity. Research limitations/implications: For hotel managers the research findings illustrate the importance of brand differentiation and trust for international hotels chains and illustrate the importance of employee brand commitment in the process of building a strong band. Therefore this research has an implication not only for marketing but also for human resource managers and for hotel general managers. Originality/value: The value of this research resides in the exploration between service brand equity and employee brand commitment. The literature on service marketing emphasizes the link between employee and service quality but to the authors' knowledge little research has explored the link between the service brand and its employees. © Emerald Group Publishing Limited.